Estudo da capacidade preditiva dos métodos de avaliação nutricional global e suas variáveis nas complicações pós operatórias do câncer gástrico - Silva, Luciana de Souza Penhalbel (2013)
Introduction: Malnutrition adversely affects the patients who have gone through oncological surgery, leading to greater surgical morbidity and mortality. However, there is still the need to establish a golden rule for nutritional evaluation as a predictive factor in the morbimortality of these patients. The objective of this study was to analyze and compare the capacity of nutritional assessment methods in the prognosis of complications in patients submitted to gastric cancer gastrectomy. Methods: The method used was the prospective observational study of 66 gastric cancer patients who were submitted to gastrectomies. Assessment was made through the following nutritional evaluation methods: Subjective Global Assessment of Nutritional Status (SGA), Objective Nutritional Evaluation (ONE) and the Nutritional Risk Index (NRI). Beyond the surgical risk by means of a prognostic index of Sheffield (SPI). The results were compared to surgical morbimortality, total duration of hospitalization and stay in the Intensive Care Unit (ICU). The stage of the disease was based on the American classification for gastric cancer. For the estatiscal analyses were used Kaplan-Meier method, log-rank test, t test or non-parametric Kruskal-Wallis test. Associations were evaluated by the Pearson chi-square test, or by the Fisher exact test whenever recommended. Results: Malnutrition was present in 80.7%, 66.7% and 85% in the SGA, ONE and NRI, respectively. The SPI demonstrated a high surgical risk in 92% of patients. There was a slight agreement in the SGA and NRI (Kappa=0.30). The SGA results showed that the malnourished patient (p<0.05) remained in the hospital for a longer period time. Most of the patients (62.9%) were at an advanced stage of the disease which was associated to an increase in complications (p<0.01) and isolated cases of pneumonia that were associated with lymphopenia (p<0.05). Conclusion: The SGA and the NRI were the methods that had the closest agreement in the results. The SGA was the only method that demonstrated an association between malnutrition and longer stay in hospital. Pneumonia was observed in the presence of advanced tumors and lymphopenia, thus increasing the duration of hospitalization and stay in the ICU (p<0.05).